2018
DOI: 10.1002/advs.201800514
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctionality from Synergy: CoP Nanoparticles Embedded in Amorphous CoOx Nanoplates with Heterostructures for Highly Efficient Water Electrolysis

Abstract: Hydrogen production from renewable electricity relies upon the development of an efficient alkaline water electrolysis device and, ultimately, upon the availability of low cost and stable electrocatalysts that can promote oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). Normally, different electrocatalysts are applied for HER and OER because of their different reaction intermediates and mechanisms. Here, the synthesis of a heterostructured CoP@a‐CoOx plate, which constitutes the embedded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(91 citation statements)
references
References 49 publications
1
84
0
Order By: Relevance
“…Lattice spacing is measured to be 0.23 nm, corresponding to the (100) facet of Ru and no lattice fringe of Cu is observed (Figure 1g). [26,27] To optimize the catalytic performance,t he channel-rich RuCu NSs were loaded on carbon black (Supporting In-formation, Figure S4) and annealed in air for 1hat different temperatures (that is,2 50 8 8C, 300 8 8Ca nd 350 8 8C, denoted as RuCu NSs/C-T, T = 250 8 8C, 300 8 8C, 350 8 8C, respectively) (Supporting Information, Figure S5). All the results indicate that RuCu NSs are composed of crystallized Ru and amorphous Cu.…”
Section: Resultsmentioning
confidence: 67%
“…Lattice spacing is measured to be 0.23 nm, corresponding to the (100) facet of Ru and no lattice fringe of Cu is observed (Figure 1g). [26,27] To optimize the catalytic performance,t he channel-rich RuCu NSs were loaded on carbon black (Supporting In-formation, Figure S4) and annealed in air for 1hat different temperatures (that is,2 50 8 8C, 300 8 8Ca nd 350 8 8C, denoted as RuCu NSs/C-T, T = 250 8 8C, 300 8 8C, 350 8 8C, respectively) (Supporting Information, Figure S5). All the results indicate that RuCu NSs are composed of crystallized Ru and amorphous Cu.…”
Section: Resultsmentioning
confidence: 67%
“…To further evaluate its potential application value, we compared the overpotential of M−Co 3 O 4 /CoO x P y with other reported Co‐based catalysts as listed in Table S1. We show that the OER activity of M−Co 3 O 4 /CoO x P y is comparable, if not better than most of the Co‐based materials including a few CoP catalyst, suggesting the synergistic effect between the heterogeneous Co 3 O 4 /CoO x P y structure and possibly also among the mixed CoO, Co 2 P and CoP species . Figure b shows the corresponding Tafel plot, where the potentials are plot versus the logarithm of current density .…”
Section: Resultsmentioning
confidence: 87%
“…The M−Co 3 O 4 /CoO x P y showed a higher C dl of 8.1 mF cm −2 and a larger electrochemical active surface areas (ECSA) of 39.1 cm 2 compared with these of M−Co 3 O 4 (5.1 mF cm −2 and 24.6 cm 2 ), despite of its lower specific surface area. The result suggested that there are more active sites on the surface of M−Co 3 O 4 /CoO x P y , possibly derived from the heterogeneous structure and the synergistic effect between Co 3 O 4 and CoO x P y . The charge‐transfer in both catalysts were also studied using electrochemical impedance spectroscopy (EIS) as shown in Figure d.…”
Section: Resultsmentioning
confidence: 99%
“…The other peaks in Co 2p 3/2 of CoP correspond to Co 3+ /Co 2+ (780.7 eV,7 82.5 eV) and satellite peaks (784.5 eV). [5c] In addition, OÀCo (531.2 eV) and OÀC( 532.1 eV) peaks can be seen in all the samples, [13] and the O À P (533.1 eV) peak is observed in CoP/Co-MOF and CoP. N À Co and N À Hp eaks are both observed in Co-MOF and CoP/Co-MOF, [12] while the N À Ppeak is only found in CoP/Co-MOF due to the partial phosphorization process.…”
mentioning
confidence: 93%